Pemodelan Arsitektur Enterprise dengan TOGAF pada SMK Bhakti Mulia Pare - Adimas Ketut Nalendra; Wing Wahyu Winarno; Andi Sunyoto (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
Usage of Information Technology (IT) in the governance of secondary schools, especially vocational Bhakti Mulia Pare has not fully own architecture and use of certain framework, the use of IT is currently only to satisfy a need for a part or division terntentu. Enterprise architecture planning aims to align business strategy and technology strategy of an organization. To align the blueprint dibutuhak an information system. TOGAF is a framework that can assist in analyzing an information system blueprint. The results of the analysis of TOGAF in the form of the proposed business architecture, application architecture, data architecture and technology architecture. Ujikelayakan EA using EA Scorecard to generate more than 50% valid. Keywords—Enterpirse Arhitecture, TOGAF, EA Scorecard